A methodological study on domestic violence among married women to develop screening tool in selected rural and urban areas, sri amritsar, Punjab - Kaur Malhi, Guramritpal; Kaur, Sukhbir; Kaur, Gurjit (International Journal of Nursing Research, 2023)
Background: Intimate partner violence against women is seen in all cultures. In the local language, available questionnaires are either too exhaustive or inadequate to assess domestic violence comprehensively Objectives: The present study objective is to develop screening tool on domestic violence for married women, to establish the content validity of the tool and to establish the reliability of the tool. intimate partner violence Materials and methods: The present study was methodological psychometric evaluation conducted on 300 married women in selected rural and urban areas, Sri Amritsar. The sample was selected through Purposive sampling technique. Kaiser-Meyer-Olkin (0.61) and Bartlett‟s Test of Sphericity (p-value 0.00) validated a 36-item, a selfadministered questionnaire. An Eigen value > 1 and a loading factor > 0.3 for each component were considered as indices for extracting domestic violence components. Results: The instrument was completed by 300 women. According to factors of domestic violence there was 50.06% of married women were having Financial domestic violence, followed by 44.28% of Physical domestic violence followed by 44.17% were having Emotional domestic violence and 36.21% were having Sexual domestic violence. The Cronbach‟s alpha coefficients were 0.754 of the questionnaire. and S-CVI ( Scale content validity index) for the domestic violence questionnaire was 1.0 and CVI (content validity index ) for maximum items was between 0.8 – 0.9. Conclusions: The used instrument for measuring domestic violence had desirable validity and reliability and can be used as a suitable instrument in health and social researchers in the local population